Outcomes of pregnancies complicated by systemic lupus erythematosus (SLE) - Podjanee Phadungkiatwattana (2018)
Objective: To assess the outcomes of pregnancies complicated by systemic lupus erythematosus (SLE) and evaluate the clinical course of the disease during pregnancy. Material and Method: The database of high-risk pregnancies between 1995 and 2006 was prospectively collected and searched for pregnancies with SLE. The medical records were reviewed. Results: Sixty-eight pregnant women were identified during the period of the present study. Of 61 (89.7%) live births, 27 (39.7%) had preterm delivery and 20 (29.4%) had fetal growth restriction. Mean gestational age was 35.6 ± 4.2 weeks. Mean neonatal birth weight was 2322 ± 781 grams. There were seven (10.3%) perinatal deaths. Maternal SLE flares occurred in 20 (29.4%), seven in the first trimester, eight in the second trimester, five in the third trimester, and none in the post partum period. Preeclampsia is the most common maternal complication (20.6%). There was a higher rate of flares if the pregnancy occurred while the disease was active. The predictor of poor pregnancies outcomes included flare-up of the disease, renal involvement, hypertension, and conception while the disease is active. Conclusion: Active SLE prior to pregnancy is associated with a less favorable maternal and fetal outcome. Hypertension increased the risk of fetal loss and adverse outcome.